DRAINAGE CO-EFFICIENT FOR MOLE DRAINS TO RECLAIM DEGRADED VERTISOLS OF GODAVARI BASIN - A. SAMBAIAH*, M. RAGHU BABU, G. RAVI BABU, G.V. LAKSHMI; S.B.S. NARASIMHA RAO (The Journal of Research ANGRAU, 2020)
Determination of drainage co-efficient for mole drains for Kapileswarapurammandal, East Godavari district of Andhra Pradesh was carried out by considering 26-Years daily maximum rainfall events, normal daily rainfall, Weibul’s (5-Year Return Period) rainfall event, cumulative 10-day to 1-day maximum rainfall value, best fitting distribution (5-Year Return Period) value. Among all, Weibul’s (5-Year Return Period) rainfall event and best fitting distribution (5-Year Return period) rainfall are close to each other and hence, the observed 1-day maximumrainfall event, which is also arrived using Weibul’s method i.e. 157.0 mm of 1-day maximum event was considered for estimation of corresponding direct runoff. An event of 157.0 mm rainfall has potential for damaging the surface layers of the vertisols by ponding and subsurface layers by waterlogging. To evacuate both surface and subsurface matrix for avoiding the land degradation, effective drainage systems are to be designed and made functional. To do so, the direct runoff was estimated using SCS-CN method which is found to be 101.4 mm needs to be drained. The difference between the 1-day maximum rainfall event and the direct surface runoff (101.4 mm) is the abstraction amount available for preferential flow into the mole drains, i.e.55.6 mm d-1. This becomes the drainage co-efficient requirement for the mole drains of the study area, which can be used in Hooghoudt’s equation to arrive at the mole drain spacing. In this study, mathematical models were developed for estimation of mole drain co-efficient (M.D.C.) for the study area and found that the it relates to 1- day maximum with 2nd order polynomial equation with co-efficient of determination of 0.9911 and it relates to return period with logarithmic equation with co-efficient of determination of 0.9869.